Three-dimensional slope stability analysis incorporating unsaturated soil properties in Singapore - Ip, Sabrina Chui Yee (2021)
Rainfall-induced slope failure is a natural hazard that occurs in many parts of the world. To identify areas where rainfall-induced slope failure may potentially occur in Singapore, a slope susceptibility map of needs to be developed. Majority of the slope failures occurred in residual soils during or after torrential rainfall. In Singapore, residual soils are generally unsaturated because of the deep groundwater table. Hence, it is important to incorporate unsaturated soil properties (i.e. soil–water characteristic curve) in the development of slope susceptibility map in Singapore. In this study, spatial distributions of saturated and unsaturated soil properties were estimated using ordinary kriging. Seepage analysis of zonation in the residual soil from Bukit Timah Granite was carried out using Transient Rainfall Infiltration and Grid-Based Regional Slope-Stability Model (TRIGRS), a publicly available software. The resulting pore-water pressures from the seepage analyses were incorporated into Scoops3D for three-dimensional slope stability analyses. Most areas in the investigated zone were found to have high factors of safety. Only 0.054% of the investigated zonation was associated with very low factors of safety.